Nutrient recovery from domestic effluent using an indigenous strain of scenedesmus sp - Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Buyong, Ramlah; Hashim, Nor Haslina; Matias-Peralta, Hazel Monica; Mohd-Kassim, Amir-Hashim (WILEY, 2018)
The performance of a Scenedesmus sp. in the phycoremediation of domestic secondary effluents and the high-quality production of the effluents for safe disposal were investigated in the current work. An indigenous strain of a Scenedesmus sp. was obtained from a sludge thickness basin at a wastewater treatment plant. The characteristics of this microalgae were identified using a molecular analysis based on 18S ribosomal RNA sequences. The phycoremediation process was conducted in a photoreactor tank (5 L) with five different concentrations of a Scenedesmus sp. (between 105 and 106 cells mL--1). The reactors were then placed outdoors (exposed to natural environmental conditions) for eight days. The Scenedesmus sp. had the ability to remove 91.86, 98.15 and 93.11% of total nitrogen (TN), total phosphorus (TP) and total organic carbon (TOC), respectively, and reduce biochemical oxygen demand (BOD), chemical oxygen demand (COD) and total suspended solid (TSS) by 86.5, 69.9 and 76%, respectively, at a concentration of 106 cells mL--1. Moreover, the increase in the pH value during microalgae activity contributed to the increases in nutrients and characteristics percentage removal. The treated secondary effluents generated from the phycoremediation process after eight days met the EQA 1974 (Regulation 2009) sewage sludge (standard A) in terms of TN and TP but was still not under the permissible limits for BOD, COD and TSS. In conclusion, an indigenous Scenedesmus sp. was efficient in enhancing the quality of secondary wastewater to meet the standards required for reuse or safe disposal.